Molecular Subtypes of Breast Cancer in South Asian Population by Immunohistochemical Profile and Her2neu Gene Amplification by FISH Technique: Association with other Clinicopathologic Parameters. Issue 6 (13th September 2014) - Hashmi, Atif Ali; Edhi, Muhammad Muzzammil; Naqvi, Hanna; Khurshid, Amna; Faridi, Naveen
Abstract Molecular breast cancer subtypes were defined by gene expression prolife; however, immunohistochemical (IHC) expression can categorize breast cancers analogous to gene expression profiling. We aimed to evaluate distribution of these molecular breast cancer subtypes in our population and their association with clinocopathologic parameters. We retrospectively analyzed 1, 104 cases of primary breast cancers over 3 years duration. ER, PR, Her2neu IHC staining, and subsequent fluorescent in situ hybridization studies (Her2neu gene amplification in cases with 2+ IHC staining) were performed to categorize breast cancer subtypes. Luminal A breast cancers were most frequent (45.8%) followed by triple negative (18.6%), luminal B (17.8%) and Her2neu (17.8%) subtypes. We found a strong association of breast cancer subtypes with tumor grade and Ki67 proliferation index with triple negative cancers being associated with higher grade and proliferation index. Significant association was seen with age groups, luminal A subtype occurring at a slightly older age, whereas triple negative and Her2neu cancers were more frequent in younger age group. We found a higher proportion of triple negative cancers in our set up, and they were found to have high‐tumor grade and proliferation index along with presentation at younger age. As these cancers are associated with BRCA 1 mutations and abnormal BRCA 1 pathways, we suggest that large scale studies should be done to evaluate BRCA 1 mutations and abnormal BRCA 1 pathways in our population to establish risk factors for this highly aggressive tumor subtype.